Effectiveness of vasodilatory medications on radial artery spasm in patients undergoing transradial coronary artery procedures: a systematic review protocol. (August 2016) - Curtis, Elizabeth; Fernandez, Ritin; Lee, Astin
Abstract : Review question/objective: The quantitative objective is to identify the effectiveness of vasodilatory medications on radial artery spasm in patients undergoing transradial coronary artery procedures.